1988
DOI: 10.1128/mcb.8.3.1236
|View full text |Cite
|
Sign up to set email alerts
|

Differential stimulation of sea urchin early and late H2B histone gene expression by a gastrula nuclear extract after injection into Xenopus laevis oocytes.

Abstract: Sea urchin early histone genes are active in preblastula embryos; late histone genes are maximafly expressed during subsequent stages of embryogenesis. We used the Xenopus laevis oocyte to assay for trans-acting factors involved in this differential regulation. Sea urchin nuclear proteins were prepared by extracting gastrula-stage chromatin successively with 0.45, 1, and 2 M NaCl. We injected three fractions into oocytes along with plasmids bearing sea urchin early and late H2b histone genes. While neither the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Micro-injection of gene constructs with intact or mutant promoters or hybrid promoters containing individual control elements has been widely used in determining cis-active elements of a variety of genes, regardless of their species of origin (30,31). Coinjection of putative regulatory proteins, or cDNA coding for such factors, also allows functional testing of transactive components of gene regulation (31)(32)(33)(34)(35)(36).…”
Section: Original Articlesmentioning
confidence: 99%
“…Micro-injection of gene constructs with intact or mutant promoters or hybrid promoters containing individual control elements has been widely used in determining cis-active elements of a variety of genes, regardless of their species of origin (30,31). Coinjection of putative regulatory proteins, or cDNA coding for such factors, also allows functional testing of transactive components of gene regulation (31)(32)(33)(34)(35)(36).…”
Section: Original Articlesmentioning
confidence: 99%
“…Their transcription is shut off in mesenchyme blastula embryos (8-10). The transition from a transcriptionally active to an inactive state of the early histone genes is accompanied by structural alterations of their chromatin arrangement (11-13).Molecular genetic analysis of many polymerase II promoters has revealed that optimal and accurate initiation of transcription requires a cooperative interaction of transacting factors with multiple cis-acting transcriptional elements (14)(15)(16)(17).Recent studies on the factors involved in the transcriptional control of the sea urchin histone H1 and H2B genes have identified basal and ontogenic transcriptional elements involved in the transition from early to late gene expression during development (18,19). Furthermore, they have shown that an embryo-specific repressor element, the CCAAT displacement factor, prevents the interaction of a positive trans-acting factor with the CCAAT box ofthe sperm-specific H2B-1 gene (20) and in so doing may block transcription in the embryo.…”
mentioning
confidence: 99%
“…Recent studies on the factors involved in the transcriptional control of the sea urchin histone H1 and H2B genes have identified basal and ontogenic transcriptional elements involved in the transition from early to late gene expression during development (18,19). Furthermore, they have shown that an embryo-specific repressor element, the CCAAT displacement factor, prevents the interaction of a positive trans-acting factor with the CCAAT box ofthe sperm-specific H2B-1 gene (20) and in so doing may block transcription in the embryo.…”
mentioning
confidence: 99%
“…It has been demonstrated that protein-free plasmid DNA injected into oocyte nuclei becomes organized in a nucleosomal chromatin structure, but only a very small fraction of these 'minichromosomes' is transcriptionally active whereas the majority of the molecules persists as inactive chromatin [4][5][6]. Recently, attention has been focussed on the interdependence of chromatin assembly with formation of stable transcription complexes using this type of in vivo gene expression assay [7,8]. Here, we used an S-150 extract prepared from X. laevis oocytes [9] for controlled in vitro chromatin assembly.…”
Section: Introductionmentioning
confidence: 99%